The Effect of Different Types of Aerobic Protocols with Different Intensity and Duration on the Management and Recovery of Breast Cancer in Preclinical Studies: A Brief Review - Khosro Jalali-Dehkordi; Navid Abedpoor (Vesnu Publications, 2021)
Exercise is effective in preventing and controlling the progression of breast cancer. By inhibiting the growth and metastasis of cancer, physical activity can help manage and delay the side effects caused by cancer and its treatment. It can also increase people's tolerance and adherence to treatment and improve their quality of life. As ethical limitations exist for studying human samples, animal models are suitable for identifying the mechanism of the effect of various diseases in the body and the impact of proposed treatments. Based on these studies, continuous moderate aerobic and intermittent intense exercises, each through different mechanisms, can help prevent cancer, accelerate the treatment process, and reduce and delay complications caused by the disease or its medical and pharmaceutical treatment methods. However, more research is needed to study the molecular mechanisms of the effect of these exercise protocols in greater detail. Finally, research shows that the intensity, duration, and frequency of exercise are important factors that determine the treatment results in cancer control. Therefore, conducting more preclinical and clinical studies in this field is strongly recommended.